Sistem Penilaian Kinerja Berbasis Online di Fakultas RST - Musrifah, Ai; Andriayani, Shela (Jurnal Media Teknik dan Sistem Industri, 2022)
The RST Faculty has three study programs with 38 employees, some of which are lecturers and teaching staff. To support the success of achieving the vision and mission of the Faculty, one of which is the performance of the employees. The process of evaluating employee performance must be carried out by the faculty. Performance Appraisal is a systematic evaluation in understanding employee performance and abilities, so that faculties can plan salary increases, promotions, determine outstanding lecturers and teaching staff or can be used as a basic assessment of demotion and termination of employees' employment. An employee performance appraisal system needs to be designed as the basis for a performance measurement tool to make it easier for employees and faculty in the process of managing performance appraisals that can be done online. The software engineering methodology is made using the Waterfall method with object-oriented modeling analysis which is explained with a unified modeling language (UML) diagram. The results of the online-based performance management system design are reporting the performance of lecturers, educators, the assessment process and seeing the results of the assessment carried out online.Â Fakultas RST memiliki tiga Program Studi dengan jumlah karyawan 38 orang, ada yang berstatus dosen dan tenaga pendidik. Untuk menunjang keberhasilan pencapai visi dan misi Fakultas salah satunya adalah kinerja dari karyawan. Proses evaluasi kinerja karyawan harus dilakukan oleh fakultas. Penilaian kinerja yaitu evaluasi sistematis dalam memahami kinerja dan kemampuan karyawan, sehingga fakultas dapat merencanakan kenaikan gaji, promosi, penentuan dosen dan tenaga pendidik berprestasi ataupun dapat dijadikan sebagai penilaian dasar penurunan jabatan dan pemutusan hubungan kerja karyawan. Sistem penilaian kinerja karyawan perlu dirancang sebagai dasar alat pengukuran kinerja supaya memudahkan karyawan dan fakultas dalam proses pengelolaan penilaian kinerja yang dapat dilakukan secara online. Metodologi rekayasa perangkat lunak dibuat menggunakan metode waterfall dengan analisis permodelan berbasis orientasi objek yang dijelaskan dengan diagram unified modelling language (UML). Hasil perancangan Performance management system berbasis online yaitu pelaporan kinerja dosen, tenaga pendidik, proses penilaian dan melihat hasil penilaian dilakukan secara online.Â